设函数f(x)=lnx+
(1)求实数a的取值范围; (2)若x1∈(0,1),x2∈(1,+∞),求证:f(x2)-f(x1)>e+2-
|
(1)函数的定义域为(0,1)∪(1,+∞)
求导函数f′(x)=
-1 x
=a (x-1)2 x2-(a+2)x+1 x(x-1)2
∵函数f(x)=lnx+
在(0,a x-1
)内有极值1 e
∴f′(x)=0在(0,
)内有解,令g(x)=x2-(a+2)x+1=(x-α)(x-β)1 e
∵αβ=1,不妨设0<α<
,则β>e1 e
∵g(0)=1>0,
∴g(
)=1 e
-1 e2
+1<0,a+2 e
∴a>e+
-21 e
(2)证明:由f′(x)>0,可得0<x<α或x>β;由f′(x)<0,可得α<x<1或1<x<β
∴f(x)在(0,α)内递增,在(α,1)内递减,在(1,β)内递减,在(β,+∞)递增
由x1∈(0,1),可得f(x1)≤f(α)=lnα+a α-1
由x2∈(1,+∞),可得f(x2)≥f(β)=lnβ+a β-1
∴f(x2)-f(x1)≥f(β)-f(α)
∵αβ=1,α+β=a+2
∴f(β)-f(α )=2lnβ+a×
=2lnβ+a×α-β (β-1)(α-1)
=2lnβ+β -
-β1 β 2-(a+2) 1 β
记h(β)=2lnβ+β -
(β>e)1 β
则h′(β)=
+1+2 β
>0,h(β)在(0,+∞)上单调递增1 β2
∴h(β)>h(e)=e+2-1 e
∴f(x2)-f(x1)>e+2-1 e